A highly fluorescent adenine derivative and its interaction with iron ions. Issue 22 (31st May 2019) - Liu, Zhengzhou; Lu, Zheng; Peng, Weifeng; Liu, Yang; Hu, Jianghuai; Zeng, Ke; Yang, Gang
Abstract: In this paper, an adenine-derived fluorescent chromophore (HCC-APA) was synthesized to detect its interaction with iron ions. The results showed that a large stokes shift ( υ  = 10981.5 cm −1 ) fluorescence of the HCC-APA was appeared. The fluorescence quantum yields of HCC-APA in DMF and THF were 3.49% and 17.54%, respectively, demonstrating its higher fluorescence performance than unmodified adenine. Besides, the fluorescence quenching of HCC-APA with iron ions was further detected. Fluorescence titration experiments confirmed that the detection limit of HCC-APA for Fe 3+ was 3.69 μM. The interaction between iron ions and HCC-APA was investigated by continuous variable method, indicating that the binding ratio is 1:1. And the interaction site was deeply explored by 1 H NMR and molecular simulation. Graphical abstract: Image 1